Stability Improvement of Renewable Energy Integrated Power Network Through Coordination of PSS, ISFCL, and STATCOM - Afrasiyab Khan; Babar Hussain; Addy Wahyudie; Ruhul Amin Khalil (IEEE Access)
Wind energy is a promising solution to meet growing global energy demands; however, its intermittent nature and low system inertia introduce significant challenges to power system stability. This paper addresses these issues by applying a coordinated deployment of a Power System Stabilizer (PSS), an Inductive Superconducting Fault Current Limiter (ISFCL), and a Static Synchronous Compensator (STATCOM) to the IEEE 9-bus system. Type 1 and Type 3 wind farms are integrated into the network, and system performance is evaluated using Sum of Mean Deviations (SMD) and Critical Clearing Time (CCT). The dual-input PSS enhances damping of rotor oscillations, ISFCL limits peak fault currents by up to 37%, and STATCOM, optimized using the Hooke & Jeeves method, reduces voltage dip by 0.3 pu and strengthens Low Voltage Ride Through (LVRT) capability. The combined deployment of all three devices restores the stability indices to levels comparable to those in the base case without wind integration. Among the two wind farm types, the coordinated application proves more effective for Type 3 wind farms, which show superior damping, reduced fault current, and enhanced voltage recovery, making them more suitable for reliable grid integration. Simulations were performed in PSCAD software.